Explaining Chinese Reactions to COVID-19 During the Outbreak: A Systematic Illustration - Yuan, Meng (Frontiers in Public Health, 2021)
Objectives: This research attempts to systematically explore factors that affect different kinds of reactions, including not only different measures of risk perceptions but also public trust in different levels of governments and attentions to news. Methods: This research uses a national stratified random sample of Chinese and multiple linear regressions to explore the potential predictors of public reactions to COVID-19. Results: This research found that the effects of attentions to news, provincial experience, trust in government, demographics, and political cultures on risk perceptions depend on measures of risk perceptions—risk judgments vs. cognitive vs. affective risk perceptions. Moreover, the effect of culture on trust in government is consistent across different levels of government—trust in local, provincial, and central government; living in the epicenter of COVID-19 in China decreases trust in local/provincial government but not trust in central government; public attentions to news can bring both positive (trust in government) and negative outcomes (negative affect). Finally, it confirmed positive associations between risk perception, subjective knowledge and attentions to news. Conclusions: Findings suggest challenges for risk communication.